The mystery of God's will : what does He want for me? - Swindoll, Charles R. (Nashville, Tenn. : Word Pub., 1952)
We all face difficult decisions. How can we know that the decisions we make are in God's will? Swindoll examines this long debated subject from a balanced, biblical perspective regarding his own doubts and experiences. For anyone who's ever doubted God's will, or for those who are convinced of it in every situation, this book will be a real eye-opener.
pt. 1. The buffetings of God's will -- ch. 1. A process and a puzzle -- ch. 2. God decrees ... God permits -- ch. 3. Moving from theory to reality -- ch. 4. Fleshing out the will of God -- ch. 5. Another deep mystery: God's sovereignty -- ch. 6. Reading God's mysterious lips -- pt. 2. The blessings of God's will -- ch. 7. The magnificent Chesed of God -- ch. 8. God's mysterious immutability -- ch. 9. Can God's will make us holy? -- ch. 10. Surprised by God -- ch. 11. Closed doors, open doors -- ch. 12. A better way to look at God's will.
Includes bibliographical references (pages 219-222).
Keywords: God (Christianity) -- Will; Discernment (Christian theology); Christian life